Charisma, Networks, and Suluk Practices: Negotiating Religious Authority and Power within the MPTTI Aceh - Muhammad Suhaili Sufyan; Mawardi Mawardi; Suparwany Suparwany (Program Pascasarjana IAIN Langsa, 2026)
The emergence of the Majelis Pengkajian Tauhid Tasawuf Indonesia (MPTTI), a neo-Sufi movement affiliated with the Naqshbandi order, has transformed the contemporary religious landscape of Aceh. Despite facing strong opposition from local ulama and communities, MPTTI has expanded significantly over the past decade, particularly in southern Aceh. It employs non-confrontational strategies and extensive community networks. This study examines MPTTI’s strategies for negotiating religious authority by integrating charismatic leadership, social networks, and suluk practices to consolidate organizational legitimacy and facilitate social transformation. Using a qualitative approach, data were collected through in-depth interviews, participant observation, and document analysis, and interpreted using Foucault’s concept of power networks. The findings demonstrate that MPTTI’s expansion cannot be understood solely through theological dissemination but through the productive construction of religious authority. meanwhile, strategic relationships with local authorities and community figures help the movement navigate resistance and expand without significant confrontation. The leader’s charisma is institutionalized through suluk practices that cultivate discipline, loyalty, and spiritual legitimacy, while strategic relationships with local authorities and community figures enable the movement navigate resistance and expand its influence without open confrontation. This study contributes to the field of religion and power by demonstrating how contemporary neo-Sufi movements generate and maintain power through the intersection of charisma, disciplinary spiritual practices, and relational networks. The findings also imply that religious movements attained social legitimacy not merely through doctrinal persuasion but through adaptive patters of power that reshape local religious and social relations at local level.